2012
DOI: 10.1175/jpo-d-12-010.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Generalized Eigenvalue Problem for the Rossby Wave Vertical Velocity in the Presence of Mean Flow and Topography

Abstract: In a series of papers, Killworth and Blundell have proposed to study the effects of a background mean flow and topography on Rossby wave propagation by means of a generalized eigenvalue problem formulated in terms of the vertical velocity, obtained from a linearization of the primitive equations of motion. However, it has been known for a number of years that this eigenvalue problem contains an error, which Killworth was prevented from correcting himself by his unfortunate passing and whose correction is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Perhaps the most significant limitation is the neglect of any topographic variations. Nevertheless, aside from specific local topographic impacts [e.g., Hallberg, 1997;Killworth and Blundell, 1999;Tailleux and McWilliams, 2002;Marshall, 2011;Tailleux, 2012] and potential systematic biases through bottom pressure decoupling [Tailleux and McWilliams, 2001], our observational analysis suggests that the present arguments remain relevant even in the presence of variable bottom topography. This result is also consistent with the planetary geostrophic Rossby wave equation derived by Salmon [1994] under an assumption of uniform potential vorticity on isopycnals.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most significant limitation is the neglect of any topographic variations. Nevertheless, aside from specific local topographic impacts [e.g., Hallberg, 1997;Killworth and Blundell, 1999;Tailleux and McWilliams, 2002;Marshall, 2011;Tailleux, 2012] and potential systematic biases through bottom pressure decoupling [Tailleux and McWilliams, 2001], our observational analysis suggests that the present arguments remain relevant even in the presence of variable bottom topography. This result is also consistent with the planetary geostrophic Rossby wave equation derived by Salmon [1994] under an assumption of uniform potential vorticity on isopycnals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Maharaj et al . [] showed that there is no first baroclinic mode present at the Chile Rise 90°W38°S but that Rossby wave speed estimates in such locations can only be roughly approximated by the extended linear theory baroclinic modes 2 and 3 of Killworth and Blundell [] (see also Tailleux [] for a correction to the theory of Killworth and Blundell). In our Figure d (Peak 3), we show no significant interactions at the Chile Rise (1800 km) for disturbances traveling at planetary wave speeds but clear resonant interactions, in particular at month 500, for the slower baroclinically unstable waves (Figure c; Peak 2) in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Extended theories that consider the influence of mean flow and topography on the propagation speed change the standard dispersion relation and can account for the faster observed speed than that predicted by the standard linear theory (e.g., Aoki et al., 2009; Dewar, 1998; Killworth et al., 1997; Tailleux, 2012; Tailleux & McWilliams, 2001). The faster phase speed or more agreement between spectral peaks and the dispersion relation can be achieved by adjusting the Rossby radius of deformation in the standard dispersion relation (Osychny & Cornillon, 2004).…”
Section: Resultsmentioning
confidence: 99%